PENERAPAN KONSEP PERENCANAAN DAN PENGANGGARAN RESPONSIF GENDER (PPRG) DALAM PEMBANGUNAN DAERAH (STUDI DI PROVINSI PAPUA DAN PROVINSI DAERAH ISTIMEWA YOGYAKARTA) - Susiana, Sali (Jurnal Aspirasi, 2015)
Responsive Gender Planning and Budgeting (PPRG) is a government strategy to accelerate gender mainstreaming in development. At local level, local governments were mandated to establish the Secretariat of Local PPRG set forth by Circular Letter of the Minister of Home Affair No.050/6199/SJ. This paper is a resume of a qualitative research on implementation of responsive gender planning and budgeting concept in Papua Province and Special Region of Yogyakarta. The study showed that both provinces did not establish the Secretariat of Local PPRG because they have similar institutions that have been exist before the circular letter was made. Besides that, those provinces have legal instruments about application of PPRG which is implementated in preparing Responsive Gender Budgeting (in Special Region of Yogyakarta) and Gender Budget Statement (in Papua Province).